Experimental Study of Resonance Frequency at Prime Mover Thermoacoustic Standing Wave - Danang D. Cahyadi; Yoga N. Adhitama; Ikhsan Setiawan; Agung B. S. Utomo (Universitas Sebelas Maret, 2017)
Thermoacoustic prime movers work by using thermal energy to produce acoustic energy in the form of sound wave through thermoacoustic effect which occurs in a porous medium called stack. This paper describes an experimental study on the relation between the order of resonance frequencies generated by a thermoacoustic prime mover and the length of the resonator and the viscous penetration depth. Extending the resonator length will decreasing the resonance frequency which result in the increasing in the viscous penetration depth. Generally, the generated sound consists of only one frequency, that is the first-order one. However, under certain conditions, the sound has only the second-order frequency or comprises two frequencies of the first-order and second-order resonance frequencies. This phenomenon can be explained by considering the comparison between the effective hydraulic radius of stack () and the viscous penetration depth (). It is found that the first-order frequency appears when , while when (with calculated by using the first-order frequency) then the second order frequency is produced so that is back to a smaller value and therefore the condition of is recovered. In addition, when of the thermoacoustic prime mover will generate the first and second order frequencies together.